(untitled) (Panacea Journal of Medical Sciences, 2020)
Background: Total Anomalous Pulmonary Venous Connection (TAPVC) is congenital heart disease in which the pulmonary veins do not connect normally to left atrium. Instead they connect to right atrium, often by way of systemic vein. There may be associated cardiac malposition. Anaesthetic management requires detailed assessment of cardiac an extracardiac anomalies & its pathophysiological effects. Here we report a case of TAPVC posted for LSCS and its successful management. Case Presentation: 25yrs female known case of TAPVC at 34.5 wks of gestation admitted 3 weeks prior, Vitaly stable, we did this patient under plain epidural anaesthesia without haemodynamic instability. Conclusions: Epidural anaesthesia a better technique than general anaesthesia for supracardiac TAPVC posted for LSCS. Meticulous intraoperative monitoring is important. Cardiac Output must be maintained, avoid fall in Systemic Vascular Resistance (SVR) ensuring minimal change in shunt.